Explicit engagement principles support the performance of agroecological living landscapes (ALLs) in terms of fostering transdisciplinary research and the co-design of solutions. Poster presented at the International Forum on Agrobiodiversity Living Labs (IFALL) in Bordeaux, France - Fuchs, Lisa Elena; Triomphe, Bernard; Navarrete Cruz, Angela; Bergamini, Nadia; Piraux, Marc; Chimonyo, Vimbayi (2025)
As food systems face multiple crises, globally and locally, questioning their governance becomes increasingly important. Emerging new and alternative approaches to governing food systems aim to address territorial challenges while delivering on global threats such as climate change, biodiversity loss, soil degradation, and persistent hunger and inequality. An increasing number of these approaches are articulated in Multi-Stakeholder Platforms (MSPs), Innovation Platforms (IPs), and Living Labs (LLs). While different, all are spaces where different stakeholders actively seek to reconfigure power dynamics to address collective action problems in a participatory and democratic manner. The CGIAR Agroecology Initiative fostered the emergence of eleven agroecological living landscapes (ALLs) to foster agroecological transitions (AET) through the co-design of new production practices, value chain arrangements and business models, improve the enabling environment, and achieve behavior change. Drawing on explicit engagement principles, country teams established their respective ALLs by mapping stakeholders and defining functional boundaries. They also facilitated “vision-to-action” (V2A) processes to identify a collective vision of what a desirable future would look like, define transition pathways and behavior changes required, and develop action plans to support the AET process. To understand their functioning, we assessed whether and to which degree the nature and characterization of the ALL emergence process expressed in terms of the country team’s adherence to or engagement with the Principles of engagement correlated with the functioning and performance of the ALLs in terms of their capacity to foster actual transdisciplinary (problem-focused, solution-oriented, inclusive, reflexive) research and co-design. The ALLs vary widely in terms of stakeholder composition, physical extent, formalization of their governance and local processes, as a result of several factors, including context, previous experience with AET and multistakeholder approaches, and country team skills. Considering the role of principle-based guidance, we find that a greater degree of engagement with the six Principles of Engagement in the ALL emergence process contributes to a greater likelihood of actual co-design being fostered, which is understood as the realization of the ALL’s purpose as a transformational vehicle in support of agroecological transitions. Our research illustrates that ALLs can function as organizational vehicles that challenge the status quo, help to redistribute power, and foster co-learning and the co-design of innovations. Yet, their potential depends on participatory methods and approaches being genuinely applied to all aspects of ALL functioning. Importantly, these methods need to be used for more than context, situational, and gap analyses – but they need to be mobilized for the collective reflection and design of context-specific solutions. The formulation of different sets of guiding principles, for instance in the form of the engagement principles (Triomphe et al. 2022), the V2A process (Triomphe et al. 2024), and the ALL engagement toolkit (Voss et al. 2024), which provide practical guidance for mobilizing communities to engage in inclusive and productive co-design of solutions.